Role of Nrf2 in Disease: Novel Molecular Mechanisms and Therapeutic Approaches – Pulmonary Disease/Asthma - Audousset, Camille; McGovern, Toby; Martin, James G. (Frontiers in Physiology, 2021)
Nuclear factor erythroid 2-related factor 2 (Nrf2) is a major transcription factor involved in redox homeostasis and in the response induced to oxidative injury. Nrf2 is present in an inactive state in the cytoplasm of cells. Its activation by internal or external stimuli, such as infections or pollution, leads to the transcription of more than 500 elements through the antioxidant response element (ARE) sequence. The lungs are particularly susceptible to factors that generate oxidative stress such as infections, allergens and hyperoxia. Nrf2 has a crucial protective role against these reactive oxygen species (ROS). Oxidative stress and subsequent activation of Nrf2 have been demonstrated in many human respiratory diseases affecting the airways, including asthma and COPD, or the pulmonary parenchyma such as acute respiratory distress syndrome (ARDS) and pulmonary fibrosis. Several compounds, both naturally occurring and synthetic, have been identified as Nrf2 inducers and enhance the activation of Nrf2 and expression of Nrf2-dependent genes. These inducers have proven particularly effective at reducing the severity of the oxidatively driven lung diseases in various animal models. In humans, these compounds offer promise as potential therapeutic strategies for the management respiratory pathologies associated with oxidative stress. The purpose of this review is to summarize the involvement of Nrf2 and its inducers in acute respiratory distress syndrome (ARDS), chronic obstructive pulmonary disease (COPD), lung fibrosis in both human and in experimental models.